(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the opportunities and challenges of integrating Virtual Reality (VR) and Augmented Reality (AR) technologies into English as a Foreign Language (EFL) classrooms. The findings indicate that VR and AR create immersive and interactive learning environments that effectively enhance communicative competence, expand vocabulary acquisition, foster intercultural awareness, and increase learner motivation. At the same time, limitations such as insufficient technological infrastructure, financial costs, and lack of teacher preparation remain significant barriers to their widespread implementation. The article emphasizes that VR and AR should be considered as innovative tools that complement traditional teaching methods, offering the potential to elevate EFL pedagogy to a new level.